Cooperative Learning: An Inclusive Method To Let More Students Produce The Target Language - Rahayu, Puji (Journal of English and Education (JEE), 2007)
This paper discusses the benefits of cooperative learning method in language teaching. The writer starts with the fact that English is a very important language in this era. In the next session, the nature of cooperative learning is presented, completed with the characteristic which are positive interdependence, individual accountability, promotive interaction, interpersonal and small group skills and group processing.The application of cooperative learning the language classroom gives some benefits. Two of them are that it is inclusive in that it accepts many different student, from the high achievers to the ‘handicapped’ ones, from the rich to the poor, from different ethnic group. They are all accountable. Besides, cooperative learning method also gives more students more opportunities to produces the target language at the same time. Yet, teachers should consider the inappropriateness of the input from the students and gives corrections in the best way.